Pharmacokinetics and Drug Metabolism in Canada: The Current Landscape - Neal M. Davies (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Canadian Pharmaceutical Scientists have a rich history of ground-breaking research in pharmacokinetics and drug metabolism undertaken throughout its Pharmacy and Medical Schools and within the Pharmaceutical and biotechnology industry. The principle of drug Absorption, Distribution, Metabolism and Excretion (ADME) is the foundational basis of rationale drug-design, and pharmacotherapy. The study of ADME and its descriptive quantitative analysis is the basis of pharmacokinetics. Pharmacokinetics is fundamental in the development of a new chemical entity into a marketable product and is essential in understanding the bioavailability, bioequivalence and biosimilarities of drugs. Pharmacokinetics and drug development studies facilitate an understanding of organ-based functionality. Population pharmacokinetic variability and the modeling of drug concentrations has significant utility in translating individual response in a target patient population. This special issue serves to highlight and capture the contemporary progress and current landscape of pharmacokinetics and drug metabolism within the prevailing Canadian context. We invite articles on all aspects of Pharmacokinetics and Drug Metabolism studies highlighting the world-class research currently undertaken in Canada for this special issue.